2006
DOI: 10.1158/1055-9965.epi-05-0813
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Tumor Contains Higher N7-Methylguanine Levels in DNA than Adjacent Normal Bladder Epithelium

Abstract: Schistosoma haematobium -infected patients are more likely to develop bladder cancer and be more exposed to carcinogenic N-nitroso compounds than uninfected patients. As N7-methylguanine is a marker of exposure to methylating agents of this type, we have measured N7-methyldeoxyguanosine 3V-monophosphate (N7-MedGp) by 32 P postlabeling. DNA was isolated from 42 paired normal and tumor tissue of Egyptians with bladder cancer. N7-MedGp was detected in DNA from 93% of the tumors and 74% of the normal bladder tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The very clear differences indicate that the close correlation between the levels of DNA alkylation in normal and tumor tissue despite the very large difference in the levels of DNA damage might be partially correlated to the individual differences in modes of alkylating agent metabolism due to genetic polymorphism and/or DNA repair pathways. 55,57 Previous studies with urinary bladder 54 and other tissues 58,59 have indicated that higher levels of the DNA repair protein (i.e., O 6 -alkylguanine DNA alkyltransferase) may result in lower levels of O 6 -methylguanine in DNA. Therefore, the change towards a malignant phenotype could possibly be attributed in part to the differences in DNA repair levels.…”
Section: Discussionmentioning
confidence: 99%
“…The very clear differences indicate that the close correlation between the levels of DNA alkylation in normal and tumor tissue despite the very large difference in the levels of DNA damage might be partially correlated to the individual differences in modes of alkylating agent metabolism due to genetic polymorphism and/or DNA repair pathways. 55,57 Previous studies with urinary bladder 54 and other tissues 58,59 have indicated that higher levels of the DNA repair protein (i.e., O 6 -alkylguanine DNA alkyltransferase) may result in lower levels of O 6 -methylguanine in DNA. Therefore, the change towards a malignant phenotype could possibly be attributed in part to the differences in DNA repair levels.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that the N 7 -MeG levels in bladder cancer patients are higher in the DNA from tumour tissue than in DNA from adjacent normal epithelium (Saad et al 2006). In 42 Egyptians with bladder cancer, using the 32 P-postlabelling technique, N 7 -MedG was detected in 93% of the DNA from the tumour and 74% of the normal bladder tissue sample.…”
Section: Environmental Carcinogen Biomarker Validation 523mentioning
confidence: 99%
“…During recent years, a considerable number of studies have supported the relationship between DNA adducts and cancer risk at various sites such as liver, lung, prostate, breast and bladder (Santella et al 2005, Bak et al 2006, Rybicki et al 2006, Saad et al 2006, Zhang et al 2006, Zhu et al 2006. Although, Kyrtopoulos (2006) in his recent review referred to the potential of DNA adducts as biomarkers of cancer risk, the progress achieved in terms of the identification of environmental or genetic factors which substantially affect cancer risk among the general population is still relatively limited.…”
Section: Resultsmentioning
confidence: 99%